Micromachined adjustable hydrogel stamper for soft printing of biomolecules with adjustable-feature dimensions. - Wan Salim, Wan Wardatul Amani; Ding, Zenwen; Ziaie, Babak (American Chemical Society, 2009)
We report on the development of a hydrogel stamper with built-in reservoirs for soft-printing of biomolecules with adjustable feature dimensions. The stamper consists of potassium hydroxide (KOH)-etched silicon cavities onto which biomolecule-soaked low cross-linked density hydrogel with large pores and low mechanical strength is loaded. Application of weight to the top surface allows for a controllable protrusion of hydrogel from the opposite nozzles. Such protrusion combined with a suitable spacer between the stamper and a substrate provides a means for printing features with dimensions depending on the applied weight. Utilizing the above method, we successfully stamped bovine serum albumin conjugated with fluorescein isothiocyanate (BSA-FITC) model proteins on hydrophilic silicon substrates with a feature dimension ratio of 20:1 using a single stamper.